“Collar-like” neocommissure in mitral valve repair for extensive commissural prolapseCentral MessagePerspective - Hoshun Chong, MD, PhD; Jie Li, MD; Yunxing Xue, MD; Xiyu Zhu, MD, PhD; He Zhang, MD; Junxia Wang, MD, PhD; Hailong Cao, MD, PhD (JTCVS Techniques)
Objectives: Mitral valve repair for extensive commissural prolapse is complex; several methods have been reported with variable results. To restore the leaflet area, we introduced an innovative and effective method rather than a simple folding technique through reconstructing a neocommissure with a “collar-like” plasty technique. Methods: From 2016 to 2021, 62 patients with mitral valve extensive commissural prolapse that received the “collar-like” plasty technique were included. Results: The mean age was 51.7 ± 13.8 years, and 38 (61%) were female. Postplasty transesophageal echocardiography showed the mean transvalvular pressure gradients were 3.8 ± 1.2 mm Hg, end diastolic peak flow velocity was 1.1 ± 0.3 m/s, and coaptation height was 7.9 ± 1.1 mm. During the follow-up period of 3 to 6 months, no deaths or cardiovascular-/valvular plasty-related adverse events occurred. All patients regained their heart function and returned to normal physical activities. Conclusions: The “collar-like” plasty technique can be safely performed for patients with extensive commissural prolapse. Echocardiography revealed that the technique can restore the leaflet area of low transvalvular pressure and flow velocity.